Gel Electrolyte
Patent Information
- Application Number
- JP2020202525
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-12-07
AI Technical Summary
【0012】 本発明のゲル電解質を構成する重合体は、その原料となるモノマーのいずれもがプロトン受容性基であるイミダゾリウム塩基を有し、分子中のプロトン受容性基の数が多いため、無加湿状態において、常温でナフィオンと同等のプロトン伝導性を示し、かつ、高温(60℃を超える温度域)ではナフィオンを上回るプロトン伝導性を示す。 また、本発明のゲル電解質は、無機ナノファイバーを含んでいるため、それを含まないものに比べ高強度な物性を示す。 さらに、上記重合体は、フッ素を含まない構造であり、一般に普及しているフッ素系ポリマーと比べコスト面でも有利である。
Smart Images

Figure 0007641555000020 
Figure 0007641555000021 
Figure 0007641555000022
Abstract
Description
[Technical field]
[0001] The present invention relates to a gel electrolyte, and more specifically, to a gel electrolyte suitable as an electrolyte membrane for a fuel cell. [Background technology]
[0002] Fuel cells generate electricity directly by supplying fuel such as hydrogen and oxygen from the atmosphere to a cell and causing an electrochemical reaction between them to produce water. Because fuel cells are capable of high energy conversion and have excellent environmental adaptability, they are being developed for a variety of applications, such as small-scale local power generation, home power generation, simple power sources at campsites, mobile power sources for automobiles and small boats, and power sources for artificial satellites and space development.
[0003] Such fuel cells, particularly solid polymer fuel cells, are composed of a module in which a plurality of unit cells are arranged in parallel, each unit cell being formed by sandwiching a membrane electrode assembly, which is made up of a solid polymer electrolyte membrane and an anode electrode and a cathode electrode disposed on either side of the membrane, between a pair of separators. Conventionally, Nafion (registered trademark, the same applies hereinafter), a fluorine-based polymer, has generally and widely been used as the electrolyte membrane. However, this Nafion electrolyte membrane is expensive, and has the problem that its proton conductivity decreases significantly under high temperature and non-humidified conditions. Furthermore, in order to achieve high proton conductivity in an electrolyte membrane made of a perfluoroalkylsulfone polymer such as Nafion, the presence of water (water vapor) is essential, and a humidification system is required to operate a fuel cell equipped with such an electrolyte membrane, and there is also the problem that electricity cannot be generated in an unhumidified state.
[0004] In view of these points, in recent years, electrolyte membranes for fuel cells made of polymers other than perfluoroalkylsulfone-based polymers have been under development. For example, Patent Document 1 and Non-Patent Document 1 disclose an electrolyte membrane for a fuel cell, which contains a block copolymer of an A block capable of mutually agglomerating to form a domain at the operating temperature of the proton conductive membrane and a B block having a proton-accepting group such as a nitrogen-containing heterocycle, and a proton-donating compound such as sulfuric acid. Specifically, the block copolymer disclosed is a polymer represented by the following structural formula: However, these polymers have a proton-accepting group only on one of the raw monomers, and those cross-linked with amide bonds or the like are easily hydrolyzed, posing problems in terms of stability during high-temperature operation and long-term operation.
[0005] [ka]
[0006] [ka] [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2020-68130 A [Non-patent literature]
[0008] [Non-Patent Document 1] J. Mater. Chem. A, DOI: 10.1039 / c9ta01890e, May 3, 2019 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in consideration of the above circumstances, and aims to provide a gel electrolyte that exhibits proton conductivity equivalent to that of Nafion in the room temperature range, and that exhibits proton conductivity equal to or higher than that of Nafion in the high temperature range exceeding 60°C, while also having good strength. [Means for solving the problem]
[0010] As a result of intensive research into achieving the above-mentioned object, the inventors have found that a gel containing a polymer obtained by polymerizing an imidazolium salt having an alkenyl group and a compound having an imidazolium salt having an alkenyl group at both ends, and inorganic nanofibers, and obtained by swelling the polymer in a liquid, can serve as an electrolyte that can solve the above-mentioned problems, and have completed the present invention.
[0011] That is, the present invention provides 1. A polymer obtained by polymerizing an imidazolium salt having an alkenyl group and a compound having an imidazolium salt having an alkenyl group at both ends, inorganic nanofibers, and a liquid, a gel electrolyte in which the polymer is swollen by the liquid; 2. The gel electrolyte according to 1, in which the inorganic nanofibers are uniformly dispersed in the polymer. 3. The gel electrolyte according to 1 or 2, wherein the polymer and the inorganic nanofibers both have a network structure. 4. A gel electrolyte according to any one of 1 to 3, wherein the polymer is obtained by polymerizing an imidazolium salt having one alkenyl group on a nitrogen atom and a compound having, at both ends, an imidazolium salt having one alkenyl group on a nitrogen atom. 5. A gel electrolyte according to claim 4, wherein the imidazolium salt having one alkenyl group on the nitrogen atom is represented by the following formula (1): [ka] (In the formula, R 1 represents an alkenyl group, R 2 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms; X -represents a monovalent anion.) 6. A gel electrolyte according to claim 5, wherein the imidazolium salt having one alkenyl group on the nitrogen atom is represented by the following formula (1-1): [ka] (In the formula, X - represents a monovalent anion.) 7. The above X - But HSO4 - 5 or 6, a gel electrolyte 8. The compound having an imidazolium salt having one alkenyl group on a nitrogen atom at both ends is a gel electrolyte represented by the following formula (2): [ka] (In the formula, R 3 each independently represents an alkenyl group; Z represents a divalent organic group; Y - each independently represents a monovalent anion.) 9. A gel electrolyte according to claim 8, wherein the compound having an imidazolium salt having one alkenyl group on a nitrogen atom at both ends is represented by the following formula (2-1): [ka] (In the formula, Y - each independently represents a monovalent anion, and n represents an integer of 1 to 20. 10. The gel electrolyte of 9, wherein n is an integer from 4 to 16. 11. The above Y - However, both are HSO4 - 8. A gel electrolyte according to any one of 8 to 10, 12. The gel electrolyte according to any one of 1 to 11, wherein the inorganic nanofibers are metal oxide nanofibers. 13. The gel electrolyte of 12, wherein the metal oxide nanofibers are at least one selected from titania, alumina, silica, zinc oxide and zirconia nanofibers. 14. The gel electrolyte membrane of 12 or 13, wherein the metal oxide nanofibers are silica nanofibers. 15. The gel electrolyte according to any one of 1 to 14, wherein the liquid is at least one selected from water and sulfuric acid. 16. A gel electrolyte according to any one of 1 to 15, which is for use in a fuel cell. 17. A fuel cell comprising a gel electrolyte according to any one of 1 to 16. 18. A polymer of an imidazolium salt having one alkenyl group on a nitrogen atom, represented by the following formula (1-1), and a compound having, at both ends, an imidazolium salt having one alkenyl group on a nitrogen atom, represented by the following formula (2-1), and silica nanofibers, An organic-inorganic composite in which the inorganic nanofibers are uniformly dispersed in the polymer. [ka] (In the formula, X - represents a monovalent anion, and Y - each independently represents a monovalent anion, and n represents an integer of 1 to 20. to provide. Effect of the Invention
[0012] The polymer constituting the gel electrolyte of the present invention has, in its raw material monomers, an imidazolium base which is a proton-accepting group, and has a large number of proton-accepting groups in its molecule. Therefore, in an unhumidified state, the polymer exhibits proton conductivity at room temperature equivalent to that of Nafion, and at high temperatures (temperature ranges above 60°C), exhibits proton conductivity superior to that of Nafion. Furthermore, since the gel electrolyte of the present invention contains inorganic nanofibers, it exhibits higher strength properties than those that do not contain such nanofibers. Furthermore, the above polymer has a structure that does not contain fluorine, and is therefore advantageous in terms of cost compared to commonly used fluorine-based polymers. [Brief description of the drawings]
[0013] [Figure 1]FIG. 2 is an electron microscope photograph of the silica nanofibers obtained in Production Example 1. [Diagram 2] FIG. 2 is a graph showing the temperature change in proton conductivity in an unhumidified state for the gel electrolyte membrane prepared in Example 1, the gel electrolyte membrane prepared in Reference Example 1, and the Nafion membrane. [Diagram 3] FIG. 2 is a graph showing stress-strain curves of the gel electrolyte membranes obtained in Example 1 and Reference Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in further detail below. The gel electrolyte of the present invention is characterized in that it contains a polymer obtained by polymerizing an imidazolium salt having an alkenyl group and a compound having an imidazolium salt having an alkenyl group at both ends, inorganic nanofibers, and a liquid, and the polymer is swelled by the liquid.
[0015] The alkenyl group in the imidazolium salt and the compound having it at both ends may be linear, branched, or cyclic, and there is no restriction on the number of carbon atoms, but preferably has 2 to 10 carbon atoms, and more preferably has 2 to 5 carbon atoms. Specific examples of alkenyl groups include ethenyl (vinyl), n-1-propenyl, n-2-propenyl (allyl), n-1-butenyl, n-2-butenyl, n-3-butenyl, n-1-pentenyl, n-2-pentenyl, n-3-pentenyl, n-4-pentenyl, n-5-hexenyl, n-6-heptenyl, n-7-octenyl, n-8-nonenyl, and n-1-decenyl groups. In addition, there are no particular limitations on the substitution position of the alkenyl group in the imidazolium ring, but a structure having an alkenyl group at least on the nitrogen atom is preferred, and a structure having one alkenyl group on the nitrogen atom is more preferred.
[0016] The imidazolium salt having an alkenyl group used in the present invention is preferably, for example, one represented by the following formula (1).
[0017] [ka]
[0018] In formula (1), R 1 represents an alkenyl group, preferably an alkenyl group having 2 to 5 carbon atoms, more preferably a vinyl group or an allyl group, and still more preferably a vinyl group.
[0019] Also, R 2 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. The alkyl group having 1 to 5 carbon atoms may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, sec-butyl, t-butyl, and n-pentyl groups. Among these, R 2 is preferably a hydrogen atom.
[0020] Therefore, the imidazolium salt having an alkenyl group is more preferably one represented by the following formula (1-1).
[0021] [ka]
[0022] In the above formulas (1) and (1-1), X - The monovalent anion is not particularly limited, and may be BF4 - , PF6 - , AsF6 - , SbF6 - , AlCl4 - , NbF6 - , HSO4 - , ClO4 - , CH3SO4 - , CH3SO3 - , p-CH3C6H4SO3 - , CF3SO3 - , CF3CO2 - , (FSO2)2N - , (CF3SO2)2N -, (C2F5SO2)2N - , Cl - , Br - , I - , O.H. - However, when considering the use as an electrolyte for fuel cells, HSO4 - is preferred.
[0023] On the other hand, as the compound having an imidazolium salt having an alkenyl group at both ends used in the present invention, for example, a compound represented by the following formula (2) is preferable.
[0024] [ka]
[0025] In formula (2), R 3 Specific and preferred examples of the alkenyl group of R 1 This is similar to the example given in . The divalent organic group for Z is not particularly limited, but is preferably a divalent hydrocarbon group having 1 to 20 carbon atoms, more preferably an alkylene group having 1 to 20 carbon atoms.
[0026] Specific examples of the alkylene group having 1 to 20 carbon atoms may be linear, branched, or cyclic. Specific examples thereof include methylene, ethylene, propylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, and dodecamethylene groups. An alkylene group having 4 to 16 carbon atoms is preferred, and an alkylene group having 6 to 12 carbon atoms is more preferred. The divalent hydrocarbon group may contain O, S, NH, an amide bond, an ester bond, etc., but it is preferable that these heteroatoms or bonding groups are not present in order to ensure stability during high-temperature operation or long-term operation of devices such as fuel cells to which the gel electrolyte of the present invention is applied.
[0027] Therefore, as the compound having an imidazolium salt having an alkenyl group at both ends, one represented by the following formula (2-1) is more preferable.
[0028] [ka] (In the formula, Y - each independently represents a monovalent anion, and n represents an integer of 1 to 20, preferably 4 to 16, and more preferably 6 to 12.
[0029] Y in the above formulas (2) and (2-1) - Specific and preferred examples of the monovalent anion of X - In this case, too, when considering the electrolyte use in a fuel cell, - Both are HSO4 - is preferred.
[0030] The above monomers and dimers can be produced by known methods. The monomer may be, for example, R 2 Those in which R is a hydrogen atom can be easily obtained by mixing and neutralizing an amine such as vinylimidazole with a protonic acid that will produce the desired anion. 2 Those in which the alkyl group has 1 to 5 carbon atoms can be obtained by quaternizing amines such as vinylimidazole, or by quaternizing the amines and then mixing them with a metal salt of a desired anion for salt exchange, or by converting the amines to hydroxide anions with an ion exchange resin, and then mixing them with a protonic acid that becomes the desired anion, neutralizing the mixture, and then dehydrating the mixture. On the other hand, the dimer can be obtained, for example, by mixing a large excess of an amine such as vinylimidazole with a linear alkyl having halides at both ends to obtain a salt having quaternized ends, and then performing salt exchange in the same manner as described above.
[0031] In the present invention, the polymerization method of the imidazolium salt having an alkenyl group (hereinafter referred to as a monomer) and the compound having an imidazolium salt having an alkenyl group at both ends (hereinafter referred to as a dimer) may be appropriately selected from conventionally known polymerization methods, and for example, the monomer and the dimer may be reacted by radical polymerization to produce a polymer.
[0032] In this case, the ratio of monomer to dimer used is arbitrary. However, in consideration of further increasing the proton conductivity of the resulting gel electrolyte, the mass ratio of monomer:dimer is preferably 1:1 to 10:1, more preferably 2:1 to 8:1, even more preferably 2:1 to 6:1, and even more preferably 3:1 to 5:1.
[0033] In addition, various known polymerization initiators can be used during the polymerization. Specific examples of such polymerization initiators include persulfates, such as ammonium persulfate, sodium persulfate, and potassium persulfate; peroxides, such as benzoyl peroxide, cumene hydroperoxide, and t-butyl hydroperoxide; and azo compounds, such as azobisisobutyronitrile, azobismethylbutyronitrile, azobisisovaleronitrile, 2,2'-azobis(isobutyric acid) dimethyl, 2,2'-azobis(N-butyl-2-methylpropionamide), 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-amidinopropane) dihydrochloride, and 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride. These polymerization initiators can be used either alone or in combination of two or more. The amount of the radical polymerization initiator to be added is usually preferably 0.01 to 50% by mass based on the monomer.
[0034] The reaction temperature is preferably from 60 to 120°C, more preferably from 70 to 100°C. The reaction time is preferably 30 minutes to 24 hours, more preferably 1 to 18 hours. The polymerization reaction can be carried out in a solvent. Examples of solvents that can be used include water; hydrocarbon solvents such as pentane, hexane, cyclohexane, heptane, isooctane, toluene, xylene, and mesitylene; aprotic polar solvents such as acetonitrile, propionitrile, N,N-dimethylformamide, and N-methylpyrrolidone; halogenated hydrocarbon solvents such as dichloromethane, dichloroethane, and chlorobenzene; and ether solvents such as diethyl ether, tetrahydrofuran, dioxane, and dimethoxyethane. These solvents may be used alone or in combination of two or more.
[0035] The monomer and dimer used in the present invention are both salts, and hydrogen sulfate, which is a particularly suitable salt, is soluble in water, so it is preferable to carry out the polymerization using water as a solvent. Therefore, water-soluble persulfates and azo compounds are also preferable as polymerization initiators.
[0036] After the reaction is completed, the reaction mixture is cooled to room temperature, and then subjected to known post-treatments such as filtration, washing, and drying to obtain a polymer.
[0037] The electrolyte of the present invention is a gel electrolyte in which the above-mentioned polymer is swollen with a liquid. This liquid is not particularly limited, and various solvents that are conventionally used as electrolytes for electrochemical devices such as fuel cells can be used. Specific examples of such solvents include aqueous solvents such as water and sulfuric acid; Chain ethers such as dibutyl ether, 1,2-dimethoxyethane, 1,2-ethoxymethoxyethane, methyl diglyme, methyl triglyme, methyl tetraglyme, ethyl glyme, ethyl diglyme, butyl diglyme, ethyl cellosolve, ethyl carbitol, butyl cellosolve, and butyl carbitol; heterocyclic ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, and 4,4-dimethyl-1,3-dioxane; lactones such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, 3-methyl-1,3-oxazolidin-2-one, and 3-ethyl-1,3-oxazolidin-2-one; N-methylformamide, N Examples of non-aqueous solvents include amides such as N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and bis(2,2,2-trifluoroethyl) carbonate (TFEC); cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and vinylethylene carbonate (VEC); imidazolines such as 1,3-dimethyl-2-imidazolidinone, and nitriles such as acetonitrile and propionitrile, and these can be used alone or in combination of two or more types. Among these, in consideration of fuel cell applications, aqueous solvents are preferred, and at least one selected from water and sulfuric acid is more preferred.
[0038] The gel electrolyte of the present invention also contains inorganic nanofibers. In the present invention, the inorganic material constituting the inorganic nanofiber is not particularly limited, but in consideration of suppressing the decrease in proton conductivity of the obtained gel electrolyte and increasing its strength, metal oxides are preferred, at least one selected from titania, alumina, silica, zinc oxide and zirconia is more preferred, and silica is even more preferred. Note that in this specification, silicon (Si) is included in the metal.
[0039] The fiber diameter of the inorganic nanofibers may be in the nano range (less than 1000 nm), and is preferably from 1 to 800 nm, and more preferably from 10 to 500 nm. The fiber diameter of the nanofibers is an average value obtained by analyzing an image observed by an electron microscope, and the specific method is as described in the Examples below.
[0040] The inorganic nanofibers used in the present invention may be any fibers produced by various conventionally known techniques such as melt-blowing, flash spinning, electrospinning (ES), solution blow spinning (SBS), and centrifugal spinning. However, fibers produced by electrospinning (ES) and solution blow spinning (SBS) are preferred.
[0041] Electrospinning is a method in which a charged metal oxide solution or its precursor solution (hereinafter collectively referred to as the solution) is drawn in an electric field, causing the solution to burst due to the repulsive force of the electric charges, thereby forming extremely fine fibrous materials. The basic structure of an ES device consists of one electrode, which also serves as a nozzle for discharging the solution and applies a high voltage of several thousand to tens of thousands of volts to the solution, and the other electrode (counter electrode) that faces the first electrode. The solution discharged from one electrode turns into nanofibers through a high-speed jet in the electric field between the two opposing electrodes, and the subsequent bending and stretching of the jet, which then deposit on the surface of the other electrode, resulting in a nanofiber mat. In the present invention, a known ES apparatus can be used, and the spinning conditions in the ES apparatus, such as the distance between the nozzle tip and the counter electrode, the applied voltage, and the flow rate of the solution, may be appropriately set depending on the raw material used, the desired fiber diameter, etc.
[0042] In solution blow spinning, a solution is pumped through a spray nozzle and stretched by an air current. The solvent then evaporates, solidifying the metal oxide into fibers. The solidified fibers are then collected in an aluminum or other collector to produce a porous nanofiber sponge. In the present invention, each of the components constituting the SBS apparatus, such as a compressor and a syringe pump, can be a known device, and the solution injection rate, gas pressure, etc. can be appropriately set depending on the raw material used, the desired fiber diameter, etc.
[0043] For the purpose of decomposing organic substances contained in the produced inorganic nanofibers, the fibers may be fired at, for example, 500 to 1,000° C. for about 1 to 12 hours.
[0044] Silica nanofibers, which are suitable inorganic nanofibers in the present invention, can be produced by the above-mentioned electrospinning or solution blow spinning using a precursor solution prepared by mixing, for example, a spinning additive such as polyvinylpyrrolidone (PVP), a silica precursor such as tetraethoxysilane (TEOS), a catalytic acid such as hydrochloric acid, and a solvent such as ethanol or n-propanol. In this case, since the obtained nanofibers usually contain residual spinning additives such as PVP, it is preferable to carry out the above-mentioned calcination in order to decompose these.
[0045] The gel electrolyte of the present invention can be prepared by contacting the polymer obtained by the above-mentioned method with a liquid in the presence of inorganic nanofibers, for example by a method such as immersion, to cause the polymer to swell. In addition, the above-mentioned monomer, dimer, and polymerization initiator used if necessary can be dispersed or dissolved in a liquid, and the monomer and dimer can be polymerized in a liquid that also contains inorganic nanofibers, thereby simultaneously producing a polymer in which the inorganic nanofibers are dispersed, preferably uniformly dispersed, and gelling. In this case, a solution or dispersion containing the inorganic nanofibers, monomer and dimer can be cast onto a substrate such as a glass substrate, and then heated to polymerize, to produce a film-like gel electrolyte in which the inorganic nanofibers are dispersed, preferably uniformly, in the polymer.
[0046] Any casting method can be used, and various methods such as scraper, bar coater, brush coating, spraying, immersion, flow coating, roll coating, curtain coating, spin coating, and knife coating can be used. The heating temperature and time are the same as the reaction temperature and time during the polymerization. The film thus produced may be used after being peeled off from the substrate.
[0047] As described above, the dispersion form of the inorganic nanofibers in the polymer is preferably uniform dispersion, and more preferably a mesh structure in which fibers with a large aspect ratio in the uniformly dispersed nanofibers form intersections, in which case both the polymer and the nanofibers form a network structure.
[0048] There is no particular limitation on the thickness of the gel electrolyte, and it can be, for example, about 5 to 300 μm, but 10 to 100 μm is preferable.
[0049] The gel electrolyte of the present invention can be used as an electrolyte for various electrochemical devices, and is particularly suitable as a polymer electrolyte for fuel cells. Generally, a solid polymer electrolyte fuel cell is composed of a large number of unit cells arranged side by side, each unit cell being composed of a pair of electrodes sandwiching a solid polymer membrane and a pair of separators sandwiching these electrodes to form a gas supply and exhaust flow path. The gel electrolyte of the present invention can be used as part or all of the solid polymer membrane. EXAMPLES
[0050] The present invention will be described in more detail below with reference to Synthesis Examples, Production Examples, Examples and Reference Examples, but the present invention is not limited to the following Examples.
[0051] [1] Synthesis of raw material monomers [Synthesis Example 1] Synthesis of N-vinylimidazolium hydrogen sulfate (A) [ka]
[0052] After 60 ml of ion-exchanged water was thoroughly cooled in an ice bath, 21.7 g of concentrated sulfuric acid (manufactured by Kanto Chemical Co., Ltd.) was gradually added thereto while stirring so as not to generate heat suddenly. Next, a solution of 20.0 g of 1-vinylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.) in 60 ml of ion-exchanged water was gradually added dropwise to the obtained sulfuric acid aqueous solution while stirring on ice so as not to generate heat suddenly, and then stirring was continued for several hours. First, most of the ion-exchanged water was distilled off from this solution using an evaporator, and then a vacuum was drawn for 5 hours using a vacuum pump. 43.2 g of the target product, N-vinylimidazolium hydrogen sulfate (A), was obtained as a white solid containing a small amount of water (yield: quantitative).
[0053] [Synthesis Example 2] Synthesis of 3-vinyl-1-[8-(3-vinylimidazolidin-1-ium-1-yl)octyl]imidazolium disulfate (B) [ka]
[0054] 49.0 g of 1-vinylimidazole (Tokyo Chemical Industry Co., Ltd.) was added to a solution of 32.2 g of 1,8-dibromooctane (Tokyo Chemical Industry Co., Ltd.) in 400 ml of acetonitrile (Sanyo Chemical Industries Co., Ltd.), and the mixture was stirred at room temperature for more than two weeks. The precipitated crystals were filtered under reduced pressure using a Kiriyama funnel, and the solvent was removed by vacuum pumping to obtain 49.0 g of the intermediate 3-vinyl-1-[8-(3-vinylimidazolidin-1-ium-1-yl)octyl]imidazolium dibromide as a white solid (yield 90%). The dibromo product (3.87 g) obtained was dissolved in 20 ml of ion-exchanged water and subjected to column treatment using 30 ml of ion-exchange resin DS-2 (Organo Corporation). The eluate containing the reactant was subjected to the same column treatment several times to completely convert the bromide ions to hydroxide ions. The eluate (700 g) containing the reactant finally obtained was cooled, and concentrated sulfuric acid (Kanto Chemical Co., Ltd.) was added until the neutralization point was reached. The amount of concentrated sulfuric acid used was 1.57 g. This reaction solution was put into an evaporator to distill off water, and further dehydrated using a vacuum pump. 20 ml of a 1:1 (volume ratio) mixture of ion-exchanged water and methanol was added to the obtained jelly-like solid and stirred for several hours, after which the insoluble matter was removed by filtration through a membrane filter, and the filtrate was put into an evaporator to remove the solvent. The resulting solid was further evacuated by a vacuum pump to obtain 2.60 g of the target product, 3-vinyl-1-[8-(3-vinylimidazolidin-1-ium-1-yl)octyl]imidazolium disulfate (B), as a light brown solid (yield 62%).
[0055] [2] Production of silica nanofibers [Production Example 1] 283.1 mg of PVP (Sigma-Aldrich, Mw=1,300,000) as a spinning additive, 576 mL of tetraethoxysilane (Fujifilm Wako Pure Chemical Industries, Ltd.) and 6.62 mL of n-propanol (Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed and stirred overnight. A solution prepared by mixing 61.7 μL of 35% by mass hydrochloric acid (manufactured by Kanto Chemical Co., Ltd.), 8.0 μL of water, and 1.74 mL of n-propanol was added dropwise to this solution, and the mixture was further stirred for 60 minutes to prepare a precursor solution. The obtained precursor solution was electrospun using an electrospinning apparatus (ES2000S, manufactured by Fuence Co., Ltd.) under the conditions of an applied voltage of 20 kV, a spinning nozzle-collector distance of 15 cm, and a solution supply rate of 0.24 mL / h, and collected on an aluminum sheet as a collector. The resulting nanofibers were then peeled off and calcined in air at 600°C for 5 hours to obtain the desired silica nanofibers (average fiber diameter 70 nm). The fiber diameter of the nanofibers was calculated as the average value of 100 points in the measurement sample from secondary electron images obtained using a scanning electron microscope (JCM-5700, JEOL Ltd.) using the length measurement function of image analysis software (ImageJ, National Institutes of Health, USA). An electron microscope photograph of the obtained silica nanofibers is shown in Figure 1.
[0056] [3] Production of gel electrolyte membrane [Example 1] 20 mg of the silica nanofibers obtained in Production Example 1 was added to 0.5 mL of 0.2 mol / L sulfuric acid (Kanto Chemical Co., Ltd.), and ultrasonically treated for 30 minutes to prepare a dispersion. Separately, 0.4 g of N-vinylimidazolium hydrogensulfate (A) obtained in Synthesis Example 1 was dissolved in 0.4 mL of deionized water, and 3-vinyl-1-[8-(3-vinylimidazolidin-1-ium-1-yl)octyl]imidazolium disulfate (B) obtained in Synthesis Example 2 (mass ratio (A):(B)=5:1) and potassium persulfate (Sigma-Aldrich, 1% by mass relative to N-vinylimidazolium hydrogensulfate (A)) were added to prepare a solution. The silica nanofiber dispersion liquid prepared above was added little by little to a solution containing an imidazolium salt, and then degassed using a test tube mixer (TTM-1, manufactured by Shibata Scientific Co., Ltd.). Next, the degassed solution was spread on a slide glass and cast with a Teflon (registered trademark) scraper. The cast slide glass was placed in a glove box filled with argon gas and polymerized at 80°C for 12 hours. After polymerization, the slide glass was removed from the glove box to produce a polymer film in which the polymer absorbed moisture in the air (swollen with water). The resulting polymer membrane was peeled off from the slide glass to obtain a gel electrolyte membrane with a thickness of about 60 μm.
[0057] [Reference example 1] N-vinylimidazolium hydrogen sulfate (A) obtained in Synthesis Example 1, 3-vinyl-1-[8-(3-vinylimidazolidin-1-ium-1-yl)octyl]imidazolium disulfate (B) obtained in Synthesis Example 2 (mass ratio (A):(B)=5:1), and potassium persulfate (Sigma-Aldrich, 1% by mass relative to N-vinylimidazolium hydrogen sulfate (A)) as an initiator were dissolved in deionized water and stirred at room temperature for 2 hours. After stirring, the solution was filtered twice with absorbent cotton and degassed using a test tube mixer (TTM-1, Shibata Scientific Co., Ltd.). Next, the degassed solution was spread on a slide glass and cast with a scraper made of Teflon (registered trademark). The cast slide glass was placed in a glove box filled with argon gas, polymerized at 80° C. for 12 hours, and removed from the glove box after polymerization to produce a polymer film that absorbed moisture in the air. The resulting polymer membrane was peeled off from the slide glass to obtain a gel electrolyte membrane with a thickness of about 60 μm.
[0058] [4] Proton conductivity measurement The proton conductivity of the gel electrolyte membrane obtained in Example 1, the gel electrolyte membrane obtained in Reference Example 1, and a commercially available Nafion membrane (manufactured by DuPont) was measured by the following method. The results are shown in FIG. [Proton Conductivity] As electrochemical impedance (EIS) measurement equipment, a Solartron 1255B frequency response analyzer and a Solartron SI1287 potentiostat manufactured by Solartron were used, and measurements were performed in a constant potential mode in the frequency range of 100 mHz to 100 kHz. Specifically, a sample membrane (gel electrolyte membrane of Example 1, gel electrolyte membrane of Reference Example 1, or Nafion membrane) was sandwiched between stainless steel electrodes using an HS flat cell (manufactured by Hosen Co., Ltd.), and the resistance in the membrane thickness direction was measured at 20 to 95°C without external humidification. Note that the sample membrane from which data was recorded was stabilized for 1 hour under each test condition before measurement. Both the real and imaginary components of the impedance were measured, and it was assumed that the real z-axis intercept provides the membrane resistance, and the proton conductivity was measured based on the following formula. σ=l / SR (where σ is S cm -1 where l is the membrane thickness (cm) and S is the active area (cm 2 ), R is the membrane resistance (Ω) obtained from EIS analysis.
[0059] 2, it can be seen that the gel electrolyte membranes prepared in Example 1 and Reference Example 1 exhibit proton conductivity equivalent to that of a Nafion membrane in the room temperature range, and exhibit proton conductivity equal to or higher than that of a Nafion membrane in the high temperature range of 60 to 95° C. In particular, it can be seen that the gel electrolyte membrane containing silica nanofibers prepared in Example 1 exhibits the highest proton conductivity above 60° C. The reason why the proton conductivity of the non-humidified Nafion membrane decreases at 60°C or higher is that the water trapped in the membrane is dehydrated with increasing temperature, and the proton conduction mainly depends on the vehicle mechanism. On the other hand, the rate of decrease in the proton conductivity of the gel electrolyte membranes prepared in Example 1 and Reference Example 1 is small, which indicates that the proton conduction via the PIL does not depend much on the aqueous medium.
[0060] [5] Mechanical strength measurement of gel electrolyte membrane The stress-strain curves of the gel electrolyte membranes obtained in Example 1 and Reference Example 1 were measured using a universal testing machine (STA-1150, manufactured by A&D Co., Ltd.). The size of the samples used in the measurement was 30 mm × 10 mm. A strain was applied to each sample at a rate of 3 mm / min at room temperature, and Young's modulus was evaluated from the stress-strain curve, and tensile strength was evaluated as the stress value at the maximum value of the curve. The stress-strain curve is shown in FIG. 3, and the Young's modulus, tensile strength, and elongation at break are shown in Table 1.
[0061] [Table 1]
[0062] As shown in Table 1 and FIG. 3, it is understood that the gel electrolyte prepared in Example 1 is superior to the gel electrolyte of Reference Example 1 in mechanical strength. The Young's modulus and tensile strength increased significantly after the addition of silica nanofibers, presumably because the silica nanofibers act as temporary cross-linkers between polymer chains, creating localized regions of enhanced strength.
Claims
1. The present invention relates to a polymer obtained by polymerizing an imidazolium salt having an alkenyl group and a compound having an imidazolium salt having an alkenyl group at both ends, an inorganic nanofiber, and a liquid, wherein an anion constituting the imidazolium salt in the imidazolium salt having an alkenyl group and the compound having an imidazolium salt having an alkenyl group at both ends is HSO 4 - , ClO 4 - , C.H. 3 SO 4 - , C.H. 3 SO 3 - , p-CH 3 C 6 H 4 SO 3 - , Cl - , B - , I - and O.H. - is a monovalent anion selected from The liquid is at least one selected from water and sulfuric acid, A gel electrolyte formed by swelling the polymer with the liquid.
2. The gel electrolyte according to claim 1 , wherein the inorganic nanofibers are uniformly dispersed in the polymer.
3. The gel electrolyte according to claim 1 or 2, wherein the polymer and the inorganic nanofibers each have a network structure.
4. The gel electrolyte according to any one of claims 1 to 3, wherein the polymer is obtained by polymerizing an imidazolium salt having one alkenyl group on a nitrogen atom and a compound having an imidazolium salt having one alkenyl group on a nitrogen atom at both ends.
5. 5. The gel electrolyte according to claim 4, wherein the imidazolium salt having one alkenyl group on a nitrogen atom is represented by the following formula (1): 【Chemistry 1】 (In the formula, R 1 represents an alkenyl group, R 2 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms; X - , HSO 4 - , ClO 4 - , C.H. 3 SO 4 - , C.H. 3 SO 3 - , p-CH 3 C 6 H 4 SO 3 - , Cl - , B - , I - and O.H. - represents a monovalent anion selected from
6. The gel electrolyte according to claim 5, wherein the imidazolium salt having one alkenyl group on a nitrogen atom is represented by the following formula (1-1): 【Chemistry 2】 (In the formula, X - , HSO 4 - , ClO 4 - , C.H. 3 SO 4 - , C.H. 3 SO 3 - , p-CH 3 C 6 H 4 SO 3 - , Cl - , B - , I - and O.H. - represents a monovalent anion selected from
7. The X - But HSO 4 - The gel electrolyte according to claim 5 or 6,
8. The gel electrolyte according to any one of claims 4 to 7, wherein the compound having an imidazolium salt having one alkenyl group on a nitrogen atom at both ends is represented by the following formula (2): 【Chemistry 3】 (In the formula, R 3 each independently represents an alkenyl group; Z represents a divalent organic group; Y - are HSO 4 - , ClO 4 - , C.H. 3 SO 4 - , C.H. 3 SO 3 - , p-CH 3 C 6 H 4 SO 3 - , Cl - , B - , I - and O.H. - represents a monovalent anion selected from
9. The gel electrolyte according to claim 8, wherein the compound having an imidazolium salt having one alkenyl group on a nitrogen atom at both ends is represented by the following formula (2-1): 【Chemistry 4】 (In the formula, Y - are HSO 4 - , ClO 4 - , C.H. 3 SO 4 - , C.H. 3 SO 3 - , p-CH 3 C 6 H 4 SO 3 - , Cl - , B - , I - and O.H. - and n represents an integer of 1 to 20.
10. The gel electrolyte according to claim 9, wherein n is an integer from 4 to 16.
11. The Y - However, both are HSOs. 4 - The gel electrolyte according to any one of claims 8 to 10,
12. The gel electrolyte according to any one of claims 1 to 11, wherein the inorganic nanofibers are metal oxide nanofibers.
13. The gel electrolyte according to claim 12, wherein the metal oxide nanofibers are at least one selected from the group consisting of titania, alumina, silica, zinc oxide and zirconia nanofibers.
14. The gel electrolyte membrane according to claim 12 or 13, wherein the metal oxide nanofibers are silica nanofibers.
15. The gel electrolyte according to any one of claims 1 to 14, which does not contain an imidazolium salt represented by the following formula: 【Chemistry 5】 (wherein m is an integer from 10 to 18, and Z is Br, Cl, BF 4 , H.S.O. 4 , H 2 P.O. 4 , P.F. 6 or CF 3 SO 3 It is.)
16. The gel electrolyte according to any one of claims 1 to 15, wherein the polymer is obtained by polymerizing only an imidazolium salt having an alkenyl group and a compound having an imidazolium salt having an alkenyl group at both ends.
17. The gel electrolyte according to any one of claims 1 to 16, which is for use in a fuel cell.
18. A fuel cell comprising the gel electrolyte according to any one of claims 1 to 17.
Citation Information
Patent Citations
Electrolyte of dye-sensitized solar cells and preparation method and application thereof
CN101635200A
Preparation method of proton exchange membrane with hydrophilic / hydrophobic interpenetrating network structure
CN106876758A
Polymer solid-electrolyte fuel cell
JP1994111827A
Reinforcing material for proton conductive film, proton conductive film using same and fuel cell using same
JP2004047450A
Proton conductive film with crosslinking structure, and fuel cell
JP2020068130A